Kemungkinan Kunjungan Ulang Pasca Event Olahraga: Temuan Survei Peserta dan Pengunjung Internasional pada Asian Games 2018 - Revindo, Mohamad Dian; Widyasanti, Amalia Adininggar; Hambali, Sean; Siregar, Chairina Hanum (ASEAN Journal on Hospitality and Tourism, 2024)
The 2018 Jakarta-Palembang Asian Games is the most significant event in Asian Games history regarding contested sports, participating nations, and athletes. This study identifies the long-term benefits of the event to the host country, focusing on the international attendees’ propensity to revisit Indonesia after the event. We administered a survey throughout the two weeks of the event, yielding usable responses from 1,914 international attendees, including athletes, officials, journalists, committees, and spectators. We use the survey results to describe attendees’ evaluation of the event and Indonesia as the host country. Further, this study also estimates a multinomial logistic regression to identify the association between tourist characteristics and their intention to revisit Indonesia beyond the event. The results show that providing information and communication technology, transportation arrangement, culture, and hosting cities positively correlate with the propensity to return. In contrast, the previous visit to Indonesia has the opposite effect. International respondents mainly express their desire to revisit Indonesia on a long-stay plan. Lastly, we also discuss the academic and practical implications of our findings.